Pengaruh Penambahan Biostarter Limbah Nanas Terhadap Volume Biogas yang Dihasilkan - Siti Nurkhasanah; Sri Puji Ganefati; Muryoto Muryoto (Poltekkes Kemenkes Yogyakarta, 2011)
Cow dung in Kadipaten Village of Kedungjambal, Tawangsari, Sukoharjo had not been managed appropriately. Actually, the organic substance contained in cow dung is potentially used as raw material for biogas making. To accelerate the time needed in the biogas processing, biostarter can be added such as pineapple peels waste. The aim of the study was to identify which biostarter concentration is the most effective. The study was an experirmental one with laboratory scale and followed post-test only with control group design. In each biogas digester tank which made of 50 litre volume jerrycan consisted of 14 litre fresh cow dung, 23,4 litre dilution water and 2,6 litre pineaplle waste bio-starter concentration. The concentration variation of the biostarter were 20%, 40%, 60%, 80%, 100%. The biostarter was made by fermentation process in two times of 24 hours from the mixture of pineapple peels, tempe, banana, onion and sugar solution. The results showed that the mean volume of biogas yielded by the control group was 140 mm3, and in the 20%, 40% and 60% concentration groups were 794,0 m3, 859.7 mm3 and 925,0 respectively, but with negative flame test. Meanwhile, in the 80% and 100% concentration groups, the volume of biogas produced were 1107,0 mm3 and 1307,7 mm3 in average and show two and four minutes flame time respectively. The statistical analysis with one way anova test concluded that biostarter made from pine-apple peel waste affecting the yielded biogas volume and the most effective concentration was 100%.